RESPON PERTUMBUHAN TANAMAN TERUNG (SOLANUM MELONGENA L.) TERHADAP PEMBERIAN KOTORAN AYAM DAN GUANO WALET PADA TANAH GAMBUT PEDALAMAN (AgriPeat, 2020)
The purpose of this research was to know the use of chicken manure and guano as fertilizer and their interactions on eggplant (Solanum Melongena L.)planted on outback peatland. This study used a randomized complete block design with two factors, i.e. chicken manure and swallow guano as fertilizer, each with 3 levels of the same (a1/w1 = 5 tons/ha; a2/w 2 = 10 tons/ha; a3/w3 = 15 tons/ha). The parameters observed and measured include the plant heigh, branch number, and stem diameter of eggplant. The results showed that the single use of swallow guano had significant effect on plant height, branch number, and stem diameter of eggplant. Meanwhile, chicken manure manifest significantly to plant height and stem diameter of eggplant.The best use of swallow guano was at a dose of 15 tons/ha, while the best use of chicken manure was at a dose of 10 tons/ha.